Peran dana bergulir syariah dalam mendorong pertumbuhan UMKM - Daris, Daris; Syahman, Muhammad Syiblu; Hisyam, Naufal Nabih; Naj'la, Ummu (Maliki Interdisciplinary Journal, 2025)
Micro, Small and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy, but still face various obstacles in business development, especially in terms of access to financing. Sharia revolving funds are present as an alternative financing solution based on sharia principles such as mudharabah, musyarakah, and murabahah, which are more inclusive and equitable than conventional schemes. This study aims to analyze trends, dominant topics, and research actors related to sharia revolving funds and MSMEs using a bibliometric approach. Data were obtained from scientific articles on Google Scholar during the period 2017-2024 and analyzed using Mendeley Desktop and VOSviewer tools. The visualization results show that the dominant topics in this study are related to economic growth, the role of zakat and institutions such as BAZNAS, and government support for MSMEs in the digital ecosystem. The analysis also identified several key authors who have major contributions to this theme, such as Tati Handayani and Lina Aryani. The findings show that while sharia revolving funds have great potential in empowering MSMEs, their implementation still faces serious challenges such as low sharia financial literacy and limited channeling institutions. Therefore, there is a need for a strategy to increase literacy and strengthen the synergy between the government and Islamic financial institutions in the management of revolving funds in the future.